Blogs and Their Social Influence: Array - Bozhilova, Rozalina (Journal of Danubian Studies and Research, 2020)
The aim of this paper is to trace the development of blogs and discuss them as social media with wide influence. Research of the conditions which led to the emergence of blogs. Approach: Theoretical clarification and analysis of the phases in the development of blogs and their influence. Results: The general conclusion drawn in the paper is that development of social media and their technological improvement, their accessibility, make blogs popular, which also determine the impact that blogs have. Implications: The paper can initiate a further discussion concerning notions as social media etiquette, the power of social media, and should the social media be restricted. Value: The study will contribute to better understanding of blogs as a way of expressing public positions and values.